Modelagem da pluma de contaminação do nitrato em aquífero urbano considerando os efeitos da sazonalidade do clima em parte da Região Metropolitana de Maceió-AL - Toledo, Pedro Henrique de Omena (2016)
In many cities, groundwater is essential for human consumption. However, urban aquifers coexist with the constant risk of contamination by the various types of pollutants from heterogeneity of activities. Nitrate is the main pollutant found in aquifers in terms of abundance, and may be able to promote much harmful to human health and the aquatic environment. In this context, this study goal to evaluate the nitrate contamination plume in part of the Metropolitan Region of Maceió City and looking for evidence of the effect of recharging on pollutant dynamics. To do this, we used the MODFLOW code to simulate the steady state distribution of hydraulic load, the MODPATH for tracking particles and MT3DMS to describe the transport and fate of nitrate. The results show that the seasonality of precipitation introduced no significant influence on the water level variations in deep sedimentary aquifer as well as the contaminant dispersion. Furthermore, there is a probability that disposal of sewage in long-term on soil govern the dynamics of the nitrate concentration in 87.5% of monitoring wells.